Hermeneutics in identity formation: Paul"s use of Genesis in Galatians 4 - Punt, J. (HTS teologiese studies, 2011)
Paul’s hermeneutics, in dealing with the scriptures and traditions of Israel and his concern for a specific identity for the communities he interacted with, require attention for the reciprocal, interrelationship between hermeneutics and identity in his letters. Paul’s quotations from and allusions to the scriptures of Israel but also his argument which was a re-interpretation of the traditions of Israel, functions in Galatians 4:21–5:1 at one level as counter-argument to the position of his opponents in Galatia but, at another deeper level, also as a forceful attempt to (re)establish and reinforce the identity of the community of followers of Jesus. His appropriation of the scriptures, his revisionist interpretation of the Abraham narrative and in particular his construal of its lasting implications provided the interpretative map on which Paul plotted an emerging ‘Christian’ identity. But, reciprocally, Paul’s sense of a new or renewed identity in Christ also determined the contours of his hermeneutics.